Heat and water stress tolerance of three Soybean (Glycine Max L.) varieties under two growing conditions (Ghana Journal of Science, Technology and Development, 2025)
In this study, the growth response of three soybean varieties to heat and water stress was assessed. The three soybean varieties were subjected to water stress under two growing temperature conditions (open field condition: 25-27°C and glass house: 30-35°C). The experiment was 2 x 2 x 3 factorial arranged in a complete randomized design with three replicates. Thus two (2) growing conditions (open field and glass house), two (2) watering regimes (50% and 100%) and three (3) soybean varieties (Afakyak’, ‘Songda’ and ‘Jenguma’). Data on plant height, stem diameter, number of leaves, leaf area, chlorophyll content (SPAD) value and fresh biomass of the plants were measured at 14, 28 and 42 days after sowing (DAS). The relative injury of the three soybean varieties were also determined using a cell membrane thermostability test. The results showed that the varieties exhibited similar growth rates under each growing condition for fresh biomass, leaf area, stem diameter, plant height, number of leaves and SPAD value. There was, however, no significant difference among the tested varieties in their response to heat stress, thus implying that the three soybean varieties assessed could adapt well in the savanna agroecology of Ghana.